Ejaculatory Abstinences On DNA Fragmentation in Obese and Normal Men with Infertility and Fertility - M.S. Vyshnavi; K. Palani; S. S. Muthiah; N. Jothi Narendiran (International Journal of Pharma and Bio Sciences, 2024)
Male infertility is a growing global concern, and its association with obesity has gathered significant attention. Obesity rates are rising, and understanding the link between obesity and male infertility becomes crucial for public health in India. This study aimed to investigate the role of ejaculatory abstinence on DNA fragmentation in men, drawing a comparative analysis between obese and normal-weight individuals with both infertility and fertility statuses. A randomized controlled trial was conducted involving two groups of participants: one comprising obese men and another with normal-weight counterparts, each further divided into subgroups based on fertility status (infertile and fertile). Two semen samples were collected at a two-hour interval after 2-3 days of ejaculatory abstinence. Semen parameters, including sperm DNA fragmentation, were assessed using the halosperm technique. Preliminary findings indicate a significant impact of ejaculatory abstinence on DNA fragmentation in both obese and normal-weight individuals. Semen parameters improved in the two-hour sample in all study groups; however, the obese group showed less improvement than the non-obese groups. It was observed that DNA fragmentation significantly correlated negatively with BMI and semen parameters, including sperm count, motility, and morphology, and positively correlated with the dead sperm percentage and other lifestyle factors. The results of this study may contribute to personalized reproductive health strategies, aiding in the development of targeted interventions for couples facing infertility issues. Further research is needed to understand the molecular mechanisms underlying these observed effects and to validate the findings in larger, diverse populations.